Mackenzie role model dimensions in the quality of service, "a Prospective study of the views of a sample of Iraqi banks managers - محمد, بشرى هاشم; اسماعيل, ايسر حسن (Journal of Economics and Administrative Sciences, 2017)
The organizational integration forms a necessity according to McKinsey model, especially for service organizations. In the context of various service sector developments, importance adoption of compact mechanisms by these organizations to upgrade their services has increased and senior management must be more aware of environmental, competitive and developmental requirements. It gets more important when it shows in an organization seeking at excellence of making services within its policies and strategies. Subject organizational integration dimensions (strategy, structure, systems, style, staff, shared values, and skills) are effective components in directing behaviors of employees and organization. This motivated both researchers to consider the relationship between recognized integration according to the subject model and service quality under the dimensions of (tangibility, reliability, empty, confidentiality,  focus on customers and deal with its problems ,responsiveness ,Confidence, assurance and credibility) and in examining full subject impact as a stable variable of subject service quality as a responsive variable, especially in the current circumstances of Iraq and under restructuring process planned to government banks and growing responsibility of private banks for solving economic and social problems. For importance of subject and subject banks, (descriptive and analytical; and comparative approaches) were adopted to answer theoretical and practical questions. The aresearch involved (5) banks (2 government and 3 private). Data were collected by questionnaire of (88) paragraphs for (155) managers of government and private banks, plus interviews, observations and formal documents. The study has adapted the descriptive statistics such as(frequency distribution, percentages, the arithmetic mean, standard deviation, coefficient of variation and the severity of the response) in determining the strength of the study variables, characteristics of the sample and methods of statistics deductive nonparametric such as (Spearman correlation coefficient, regression coefficient) to test hypotheses. One of the most important conclusion is absence of  correlation between the ( style) as one of  McKenzie model dimensions, and dimensions of service quality of government and private banks equally and achievement of  correlation between the subject organizational integration and service quality in government and private banks in general. Also, achievement of incorporeal impact of subject integration and service quality generally in government and private banks.